FGF23 and Fetuin-A Interaction and Mesenchymal Osteogenic Transformation - Mattinzoli, Deborah (Int J Mol Sci, 2019)
Recently, we found a strict bone association between Fibroblast growth factor 23 (FGF23) and Fetuin-A, both involved in cardiovascular and mineral bone disorders. In this study, an uninvestigated bone marrow positivity for both was found. Though the role of exogenous FGF23 on mesenchymal cells (MSCs) was reported, no information is as yet available on the possible production of this hormone by MSCs. To further analyze these uninvestigated aspects, we studied human primary cells and mouse and human cell lines by means of immunostaining, qRT-PCR, enzyme linked immunosorbent assays, chromatin immunoprecipitation, transfection, and a streamlined approach for the FGF23–Fetuin-A interaction called Duolink proximity ligation assay. Mesenchymal cells produce but do not secrete FGF23 and its expression increases during osteo-differentiation. Fibroblast growth factor 23 is also involved in the regulation of Fetuin-A by binding directly to the Fetuin-A promoter and then activating its transcription. Both FGF23 overexpression and addition induced an upregulation of Fetuin-A in the absence of osteo-inducer factors. Fibroblast growth factor 23 and Fetuin-A promoter were increased by osteo-inducer factors with this effect being abolished after FGF23 silencing. In conclusion, both FGF23 and Fetuin-A are present and strictly linked to each other in MSCs with FGF23 driving Fetuin-A production. This mechanism suggests a role for these two proteins in the osteoblast differentiation.